2020
DOI: 10.1111/cid.12958
|View full text |Cite
|
Sign up to set email alerts
|

Comparative accuracy of cone‐beam CT and conventional multislice computed tomography for real‐time navigation in zygomatic implant surgery

Abstract: Background: Cone-beam computed tomography (CBCT) and conventional multislice CT (MSCT) are both used in zygomatic implant navigation surgery but the superiority of one technique versus the other remains unclear. Purpose: This study compared the accuracy of CBCT and MSCT in zygomatic implant navigation surgery by calculating the deviations of implants. Material and methods: Patients with severely atrophic maxillae were classified into two groups according to the use of CBCT-or MSCT-guided navigation system. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…CBCT is the primary method to acquire navigation images. It has been confirmed to gain higher accuracy than conventional multi-slice computed tomography (MSCT) due to its small voxel size (Tao et al, 2020). In CBCT, layer thickness, voxel size, threshold segmentation process, patients' movement, metal restoration, and operator's proficiency, all these factors influence accuracy (Wei et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…CBCT is the primary method to acquire navigation images. It has been confirmed to gain higher accuracy than conventional multi-slice computed tomography (MSCT) due to its small voxel size (Tao et al, 2020). In CBCT, layer thickness, voxel size, threshold segmentation process, patients' movement, metal restoration, and operator's proficiency, all these factors influence accuracy (Wei et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing high-quality CBCT or CT data for planning, producing, and executing surgical guides or navigation operations has shown similar results in surgery accuracy [ 48 , 49 ]. To analyze the planned/placed error, all eligible studies performed at least one post-operative CBCT or CT scan to merge with the pre-operative planning.…”
Section: Discussionmentioning
confidence: 99%
“…This study reported results from edentulous patients who received treatment with a non‐zygomatic implant. Wu and colleagues reported the accuracy of zygomatic implant placement in edentulous patients using dynamic CAIS, with 1.45–1.57 mm global entry deviation, 1.96–2.10 mm global apex deviation, and 2.32–2.68° angular deviation (Tao et al, 2020,b; Wu et al, 2022). The zygomatic implants can measure up to 30–50 mm, which is much longer than the conventional implants.…”
Section: Discussionmentioning
confidence: 99%